SEARCHING FOR JERUSALEM: THE END OF SOCIALIST DREAMS INWESKER’S PLAY I’M TALKING ABOUT JERUSALEM - Sameeul Haq Nazki (INJOSEDU: International Journal of Social and Education, 2025)
This study examines how Arnold Wesker presents socialist ideals and critiques social injustices in I’m Talking About Jerusalem (1960). The analysis focuses on how the play reflects Wesker’s vision of a utopian society. It critiques the socio-economic structures that perpetuate inequality and highlights the intersection of personal relationships and political ideology. The play reflects Britain’s cultural shifts during the mid-20th century as it faced the decline of empire and the rise of the welfare state. The study uses close reading to examine themes, dialogue, and character dynamics. This approach explores Wesker’s socialist rhetoric. Secondary literature and historical context provide a comprehensive understanding of the play’s socio-political significance. The study focuses on the tension between utopian dreams and the practical realities faced by the protagonists. The analysis shows how the play critiques systemic inequalities. It highlights the difficulties of realizing socialist ideals within a capitalist framework. Wesker portrays the characters’ struggles as critiques of external societal structures. He also examines their internal battle to align personal lives with political beliefs. The play shows the fragility of utopian dreams in the face of economic struggles, societal resistance, and human limits. However, it maintains an undercurrent of hope. It asserts that collective action and resilience can challenge entrenched injustices. Wesker uses domestic settings and intimate relationships to amplify his socialist message. This makes it both personal and politically powerful. The play explores the connection between political ideology and lived experience. Wesker portrays socialism as a human struggle filled with compromise and persistence. This emphasizes the continued relevance of his work in discussions on justice and equity. The play asserts the value of striving for utopian ideals, despite inevitable obstacles.